Ceilometer measurements (Arctic Data Center, 2010)
This data set contains measurements from a Vaisala ceilometer that is deployed at Summit Station, Greenland. This ceilometer points near-vertically and provides estimates of cloud base height (for up to three layers) and the total visibility, based on Vaisala's proprietary algorithm. Detailed information on these parameters and other aspects of the dataset are included in the netCDF header information for each file. The ceilometer is owned by the Department of Energy Atmospheric Radiation Measurement Program. Field operations support is provided by the National Science Foundation's Arctic Observing Network (AON) Program.